Barriers, corridors or suitable habitat? effect of monoculture tree plantations on the habitat use and prey availability for jaguars and pumas in the Atlantic Forest - Paviolo, Agustín Javier (2018)
Fil: Paviolo, Agustín Javier. Universidad Nacional de Misiones. Instituto de Biología Subtropical. Nodo Puerto Iguazú; Argentina.